2000
DOI: 10.1093/nar/28.17.3233
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional repression of BRCA1 by aberrant cytosine methylation, histone hypoacetylation and chromatin condensation of the BRCA1 promoter

Abstract: BRCA1 expression is repressed by aberrant cytosine methylation in sporadic breast cancer. We hypothesized that aberrant cytosine methylation of the BRCA1 promoter was associated with the transcriptionally repressive effects of histone hypoacetylation and chromatin condensation. To address this question, we developed an in vitro model of study using normal cells and sporadic breast cancer cells with known levels of BRCA1 transcript to produce a 1.4 kb 5-methylcytosine map of the BRCA1 5′ CpG island. While all c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 33 publications
3
50
0
1
Order By: Relevance
“…Our chromatin immunoprecipitation assays showed that both histone H3 and H4 are deacetylated in cell lines where CHFR is silent, and that 5-aza-dC and TSA act synergistically to enhance CHFR expression. Histone deacetylation thus appears to be involved in the methylation-dependent silencing of CHFR, just as in the silencing of p16INK4A, p14ARF, and BRCA1 (13,23). Nevertheless, our analysis showed that reducing DNA methylation can restore expression of CHFR despite histone deacetylation, indicating DNA methylation to be a more potent determinant of CHFR expression than histone acetylation.…”
Section: Discussionmentioning
confidence: 63%
“…Our chromatin immunoprecipitation assays showed that both histone H3 and H4 are deacetylated in cell lines where CHFR is silent, and that 5-aza-dC and TSA act synergistically to enhance CHFR expression. Histone deacetylation thus appears to be involved in the methylation-dependent silencing of CHFR, just as in the silencing of p16INK4A, p14ARF, and BRCA1 (13,23). Nevertheless, our analysis showed that reducing DNA methylation can restore expression of CHFR despite histone deacetylation, indicating DNA methylation to be a more potent determinant of CHFR expression than histone acetylation.…”
Section: Discussionmentioning
confidence: 63%
“…These data indicate that promoter hypermethylation may be secondary to the transcriptional repression and may lead to a stable inactive chromatin state, similar to the inactive X chromosome, the imprinted gene locus, and BRCA1 gene inactivation (Jeppesen and Turner, 1993;Rice and Futscher, 2000;Saitoh and Wada, 2000). Further study is necessary to clarify the precise mechanisms whereby DNA hypermethylation and histone deacetylation are involved in the alteration of chromatin structure and promoter inactivation.…”
Section: Nakayama Et Almentioning
confidence: 96%
“…This interesting difference between promoter-terminator region associations in the different breast tumor cell lines may relate to their different properties. Significantly, BRCA1 has been shown to have altered promoter DNA-protein interactions in a cell line in which BRCA1 expression is undetectable (30). Although BRCA1 repression may be caused by the associated promoter hypermethylation, an alternate explanation could be the formation of an aberrant chromatin loop between the 5Ј and 3Ј ends of the gene.…”
Section: (B) (I) Mapmentioning
confidence: 99%